FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN LOW BACK PAIN PADA PEKERJA FURNITURE - Mario Polo Widjaya; Haeril Aswar; Semuel Pala’langan (Halu Oleo University, 2014)
Low back pain is a sensation of pain in the lumbosacral and sacroiliaka region. The main causes of low back pain is mechanical factors include strain and sprain that occurs in severe and repeated physical activity. The aim of this study was investigated the relationship between stance and position of work, age, smoking habits and overweight with the low back pain incidence among furniture workers in Kambu District Kendari City. This study used cross-sectional study design. There were 100 samples in this study, chosen using cluster sampling. Data collection was derived from direct observation workplace and analyzed using Chi-Square statistical test. The study result show that 43 respondents (43%) were LBP and 57 respondents (57%) were not LBP. The low back pain incidence was found mostly in the stance and position of work (> 45o) (74,4%), age group 36-45 year (37,21%), mild smokers (60,5%) and overweight (51,2%). The bivariate analysis results show that age variable related with low back pain incidences (p=0,004), overweight variable related with low back pain incidences (p=0,011), stance and position of work variable related with low back pain incidences (p=0,00) dan smoking habits variable didn’t related with low back pain incidences (p=0,307). The conclusion of this study that there were a relationship between stance and position of worker, age and overweight with the low back pain incidences, whereas smoking habits were not relating to the low back pain incidences.Keywords : low back pain, stance and position of work, age, smoking, overweight